2016
DOI: 10.35693/2500-1388-2016-0-4-58-62
|View full text |Cite
|
Sign up to set email alerts
|

Composition of Essential Oil of Tanacetum Vulgare L. From Samara Region

Abstract: Aim - to analyze the essential oil isolated from the tansy (Tanacetum vulgare L.) flowers harvested from the spontaneous flora of Samara region. Materials and methods. The analysis was made on head flowers of Tanacetum vulgare harvested from the spontaneous flora of Samara region during the flowering stage (July), in 2016. The isolation of the essential oil was made in accordance with the Pharmacopeia of the Russian Federation XIIIth Edition. The essential oil was analyzed using a gas chromatograph coupled wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
(1 reference statement)
0
1
0
Order By: Relevance
“…It was concluded that such harvesting is possible in certain areas of the republic [12]. In the Samara region of Russia the analysis was carried out to determine the feasibility of harvesting wild raw materials of oregano [13]. In the Karachay-Cherkess Republic of Russia, a conclusion about the suitability of oregano thickets for industrial-scale use was made [14].…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that such harvesting is possible in certain areas of the republic [12]. In the Samara region of Russia the analysis was carried out to determine the feasibility of harvesting wild raw materials of oregano [13]. In the Karachay-Cherkess Republic of Russia, a conclusion about the suitability of oregano thickets for industrial-scale use was made [14].…”
Section: Introductionmentioning
confidence: 99%